The relationship between thyroid hormones and lipid profile in subclinical hypothyroidism female patients - Kazheen H. Jawzal; Mohammed A. Hami; Lina Y. Mohammed; Aveen A. Ibrahiem (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Background and objectives: Subclinical thyroid disorder is a most common subclinical disease among many medical conditions such as cardiovascular disease and subclinical Lyme disease. The aim of this study was to determine the relationship between lipid profile results, lipid ratios, and anthropometric parameters and thyroid hormones.